Analisis Pengelolaan Risiko Kebakaran Hutan Berbasis Komunitas di Kabupaten Kampar - Oktorina, Fenty Kurnia; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman (Universitas Pahlawan Tuanku Tambusai, 2024)
Forest and land fires pose a significant environmental threat in Kampar Regency, Riau Province, which is characterized by extensive and fire-prone peatlands. Community-based approaches have been identified as a vital strategy to enhance public participation in fire prevention and mitigation. This study evaluates the effectiveness of community-based fire risk management, focusing on the role of communities, challenges faced, and the policy support required. The study employs the Semantic Literature Review (SLR) method to integrate and analyze relevant literature. Data were collected from academic journals, policy reports, and other secondary sources, filtered using keywords such as